Economic and Financial Analysis Tool for Climate Change Adaptation - Steward, Peter R.; Thornton, Philip K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Aiccra EFA tool is designed to provide the high level Economic and Financial analysis (EFA) needed to inform programme development and evidence large-scale funding proposals.